2014
DOI: 10.1021/ja5040705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electron Trapping and Protonation on the Efficiency of Water-Splitting Dye-Sensitized Solar Cells

Abstract: Water-splitting dye-sensitized photoelectrochemical (WS-DSPECs) cells employ molecular sensitizers to absorb light and transport holes across the TiO2 surface to colloidal or molecular water oxidation catalysts. As hole diffusion occurs along the surface, electrons are transported through the mesoporous TiO2 film. In this paper we report the effects of electron trapping and protonation in the TiO2 film on the dynamics of electron and hole transport in WS-DSPECs. When the sensitizer bis(2,2'-bipyridine)(4,4'-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
119
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(135 citation statements)
references
References 48 publications
(128 reference statements)
15
119
1
Order By: Relevance
“…First, as noted above, irreversibility of porphyrins on TiO 2 has been previously observed (20). Also, we have observed that films of [Ru(bpy) 2 (4,4′-(PO 3 H 2 ) 2 bpy)] with poor hole transport characteristics also exhibit electrochemical irreversibility on TiO 2 (33). Second, in nonaqueous solutions TMP (27) and TTP (39) are reversible, suggesting that the irreversibility we observe is not due to fundamental chemical instability of the sensitizers.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…First, as noted above, irreversibility of porphyrins on TiO 2 has been previously observed (20). Also, we have observed that films of [Ru(bpy) 2 (4,4′-(PO 3 H 2 ) 2 bpy)] with poor hole transport characteristics also exhibit electrochemical irreversibility on TiO 2 (33). Second, in nonaqueous solutions TMP (27) and TTP (39) are reversible, suggesting that the irreversibility we observe is not due to fundamental chemical instability of the sensitizers.…”
Section: Discussionsupporting
confidence: 74%
“…Faradaic efficiency is calculated as ∼100%, and collection efficiency previously determined is 81%. (33). In the current study, the bulky sensitizers TMP and PAP had the lowest surface coverages (0.45 × 10 −7 mol/cm 2 and 0.42 × 10 −7 mol/cm 2 ); however, TTP exhibited a higher surface coverage, possibly because the tolyl groups can achieve greater planarity, and the lack of ortho-methyl groups would allow closer approach of the macrocycles.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…This viewpoint can be supported by recent reports although they did not investigate the mechanism of the proton uptake. 42,43 The existence of surface defect states is inevitable for nanostructured inorganic semiconductors, which is why R-TiO 2 still shows slow photocurrent decay despite of its single crystal nature. Moreover, proton charge compensation uptake is also common for many other metal oxides.…”
Section: Etpu Induced Photoactivity Decaymentioning
confidence: 99%